Measurement properties of the Regular Physical Exercise Adherence Scale (REPEAS) in individuals with chronic pain - Cezar Augusto Brito Pinheiro; Daniela Bassi-Dibai; André Pontes-Silva; Fábio Henrique Ferreira Pereira; Jocassia Silva Pinheiro; Cid André Fidelis-; Almir Vieira Dibai-Filho (BMC, 2024)
Abstract Objective To examine the measurement properties of the Regular Physical Exercise Adherence Scale (REPEAS) in Brazilians with chronic pain. Methods Cross-sectional and longitudinal design (washout period for reliability). The study was conducted in two Brazilian states, Maranhão and São Paulo, and included Brazilian adults, irregular exercisers, former exercisers or non-exercise practitioners, aged 18 to 59 years and with chronic pain. The instruments used in this study were: the REPEAS, the Numerical Pain Rating Scale (NPRS), the Baecke Habitual Physical Activity Questionnaire (BHPAQ), the Pain Self-Efficacy Questionnaire (PSEQ), and the Roland-Morris Disability Questionnaire for general pain (RMDQ-g). The evaluation focused on structural validity, construct validity, reliability (with standard error of measurement and minimum detectable change), internal consistency, and floor and ceiling effects. Results The two-dimensional structure was tested through confirmatory factor analysis, which resulted in adequate fit indeces: chi-square values/degrees of freedom = 1.541, Tucker-Lewis Index = 0.966, comparative fit index = 0.974, root mean square error of approximation = 0.074, and standardized root mean square residual = 0.068. Additionally, satisfactory factor loadings (> 0.40) were obtained. Test-retest reliability and internal consistency were adequate for the environmental factors domain (intraclass correlation coefficient [ICC] = 0.79, Cronbach's alpha = 0.88) and the personal factors domain (ICC = 0.97, Cronbach's alpha = 0.93). In hypothesis testing for construct validity, we observed a significant correlation with magnitude below 0.30 of the environmental factors domain of the REPEAS with RMDQ-g, PSEQ and sport domain of the BHPAQ. For the personal factors domain, we observed a significant correlation with a magnitude of 0.30 to 0.50 with RMDQ-g, PSEQ, and sport domain of the BHPAQ, and below 0.30 with leisure domain of the BHPAQ. No floor or ceiling effects were found for the REPEAS domains. Conclusion The REPEAS is a valid instrument with a two-dimensional internal structure consisting of 12 items. It has a reliable construct and is suitable for use in the clinical and epidemiological context for adults with chronic pain in Brazil.